Composite Performance Index (CPI) Method For Determining Recipients of Community-Based Development (CBD) Assistance Programs At The Dawuan Sub-District Office - Kosim, Kosim; Junaenni Januarizcha (Journal of Mathematics Instruction, Social Research and Opinion, 2024)
The eligibility of recipients of government assistance programs for rural communities is an essential problem in this study. The distribution of recipients of government assistance programs was found to be misdirected. Some rich people receive government assistance programs, but some poor people do not receive government assistance programs. One of the government assistance programs is Community Based Development (CBD), a community development activity directed at increasing community access to achieve better socioeconomic conditions than before development activities to become more independent with a better quality of life and welfare. Everyone wants this assistance program, but the eligibility level of recipients is a problem in distributing it. The research method used is Research and Development (R&D). To solve this problem, a decision support system must be created to assist the Dawuan District Office assess the beneficiaries' eligibility. The Composite Performance Index (CPI) method is needed to determine the provision of CBD assistance by using the criteria of income, housing conditions, education, and environment in the calculation. Each criterion's data from each alternative is weighted and summed to get the CPI value and used for ranking. Based on the results of system testing, the data from the calculation of the CPI method can be used as recommendations that follow the eligibility level of the beneficiaries. The most considerable CPI value is 285 on behalf of Mr. Sarip, who first prioritizes getting assistance from the CBD program. The second priority is on behalf of Mr. Budi, who has a CPI score of 265, to be the following reference as a recipient of assistance from the CBD program.